The Kulliyyah of Economics and Management Sciences: Integrating Conventional Economics with Islamic Values and Ethics - Aziz, Hassanuddeen Abd; Islam, Rafikul (IIUM Press, 2019)
The chapter describes the Kulliyyah and its various programs. Special emphasis has been placed on how the Kulliyyah develops its various programs integrating Islamic values and ethics. The chapters also highlights the achievements of the Kulliyyah over the last 35 years.